Energy performance of ground heat exchangers embedded in diaphragm walls: Field observations and optimization by numerical modelling. (March 2020) - Sterpi, D.; Tomaselli, G.; Angelotti, A.
Abstract: Ground immersed structures thermally activated by embedded heat exchangers represent a solution for building climatization, that combines efficiency, sustainability and cost saving. However, the performance of thermally activated diaphragm walls is influenced by key factors that still require insights, such as the layout of the exchanger pipe, the ratio between exposed and fully immersed parts of the wall, and the variable thermal condition at the excavation side. In this paper, these aspects are investigated first with reference to a full scale monitored diaphragm wall. From the field observations a finite element model is set up, validated by sensitivity analyses and calibrated on the monitoring data. The model is then used to attempt an optimization of the exchanger pipe layout. For given structure, ground conditions, thermal inputs and properties, the energy performance can be improved by limiting the thermal interference between pipe branches circulating fluid at different temperatures, and by taking advantage of the fully immersed part of the wall, on both faces in direct contact with the soil. A suggestion is given for enhanced pipe layouts that meet these requirements and lead to up to a 15.8% increase of exchanged heat rate for the studied case. Highlights: Energy performance of thermo-active geostructures derived from field experiments. Average heat rate 13.9 W/m 2 for diaphragm walls and 5.2 W/m 2 for base slab. Finite elements numerical model of diaphragm wall calibrated against measured data. Numerical evaluation of alternative piping layouts for optimal energy performance. 16% heat rate increase exploiting embedded part of wall and minimizing interference.